Neuronal MHC-I expression and its implications in synaptic function, axonal regeneration and Parkinson’s and other brain diseases - Cebrián, Carolina; Loike, John D.; Sulzer, David (Frontiers in Neuroanatomy, 2014)
Neuronal expression of major histocompatibility complex I (MHC-I) has been implicated in developmental synaptic plasticity and axonal regeneration in the central nervous system (CNS), but recent findings demonstrate that constitutive neuronal MHC-I can also be involved in neurodegenerative diseases by playing a neuroinflammtory role. Recent reports demonstrate its expression in vitro and in human postmortem samples and support a role in neurodegeneration involving proinflammatory cytokines, activated microglia and increased cytosolic oxidative stress. MHC-I may be important for both normal development and pathogenesis of some CNS diseases including Parkinson’s.